A new controller for DC-DC converters based on particle swarm optimization - Fermeiro, J.B.L. (2019)
Submitted by CALADO (rc@ubi.pt) on 2019-05-02T12:02:50Z No. of bitstreams: 1 6.2.32_ASC_2017.pdf: 4568623 bytes, checksum: 9d8c95b998af548946ecf35dd80c08e7 (MD5)